Deconstructing the legal framework for flood protection in Austria: individual and state responsibilities from a planning perspective. Issue 5 (4th July 2019) - Rauter, Magdalena; Schindelegger, Arthur; Fuchs, Sven; Thaler, Thomas
ABSTRACT: This article aims to analyze the legal framework for flood risk management in Austria, focusing on planning. Austria's legal basis for flood risk management is fairly complex because its federal organization involves various administrative bodies and a fragmented legal framework. Regulations are numerous, as are competencies, which poses challenges. Implementation mechanisms vary between provinces; nevertheless, provincial regulations impose basic regulations regarding the building process. Regulations concerning private protection and mitigation measures for existing buildings are, however, limited.